Perforator-Based Flap Reconstruction after Melanoma Resection: Evaluation of Oncological, Aesthetic, and Functional Outcomes - Brunetti, Beniamino; Salzillo, Rosa; Tenna, Stefania; Brunetti, Bruno; Bonetti, Mario Alessandri; Rivieccio, Antonia; Persichetti, Paolo (Journal of Reconstructive Microsurgery, 2021)
Background Evidence in literature about the best reconstructive approach after melanoma resection is controversial, with some authors advocating that tissue rearrangement flap techniques might hinder the early detection of local relapses. The aim of the present study is to evaluate oncological, aesthetic, and functional outcomes following melanoma reconstruction using pedicled perforator-based flaps.Methods The authors reviewed all patients affected by melanoma treated during a 6-year period. Demographic data, tumor characteristics, and operative variables were evaluated. Locoregional recurrence was assessed with clinical and radiological follow-up. One-year postoperatively patients rated on a 5-point Likert scale the aesthetic and functional outcomes of the procedure. Three blind observers examined preoperative and 1-year postoperative photographs and rated the aesthetic outcome of the reconstructive procedure.Results One-hundred sixty-five patients were treated with wide excision and delayed reconstruction, including pedicled perforator-based flaps in 70 patients (group A) and primary closure in 95 patients (group B). Mean Breslow thickness was 2.972 and 2.189 mm in group A and B, respectively. There was no statistically significant difference in locoregional recurrence (chi-squared test, p = 0.8333; Fisher's exact test, p > 0.9999) between the two groups. Group A reported a higher satisfaction with both the aesthetic (mean rating 4.390 in group A and 4.094 in group B) and functional (mean rating 4.732 in group A and 4.170 in group B) outcomes of the procedure, the latter being statistically significant (p = 0.0006).Conclusion This series suggests that pedicled perforator-based flaps provide optimal aesthetic and functional outcomes in melanoma reconstruction without impairing the locoregional control of the disease.
Keywords: melanoma; perforator flaps; reconstruction